2020
DOI: 10.1021/acs.jpclett.0c00214
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen Reduction Activities of Strained Platinum Core–Shell Electrocatalysts Predicted by Machine Learning

Abstract: Core−shell nanocatalyst activities are chiefly controlled by bimetallic material composition, shell thickness, and nanoparticle size. We present a machine learning framework predicting strain with site-specific precision to rationalize how strain on Pt core−shell nanocatalysts can enhance oxygen reduction activities. Large compressive strain on Pt@Cu and Pt@Ni induces optimal mass activities at 1.9 nm nanoparticle size. It is predicted that bimetallic Pt@Au and Pt@Ag have the best mass activities at 2.8 nm, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 55 publications
1
23
0
Order By: Relevance
“…713,714 In recent years, ML has proven to be a powerful tool to accelerate the screening of catalysts for energy conversion, without the need for conducting actual experiments nor a deep understanding of the underlying mechanism of the output properties. 714,715 ML has been mostly used to predict the function/activity of new materials of various complexities, e.g., single-component systems for a CO 2 RR photocathode, 716 bimetallic core−shell electrocatalysts for ORR, 717 Cu-Al electrocatalysts for CO 2 RR, 718 and graphene-supported single-atom electrocatalysts with different M-N-C coordination patterns. 719 The obtained relationships between the targeted functions/ activities, compositions, and characteristics can further guide the synthesis of optimal materials.…”
Section: Designing Optimized and Scalable Reactorsmentioning
confidence: 99%
“…713,714 In recent years, ML has proven to be a powerful tool to accelerate the screening of catalysts for energy conversion, without the need for conducting actual experiments nor a deep understanding of the underlying mechanism of the output properties. 714,715 ML has been mostly used to predict the function/activity of new materials of various complexities, e.g., single-component systems for a CO 2 RR photocathode, 716 bimetallic core−shell electrocatalysts for ORR, 717 Cu-Al electrocatalysts for CO 2 RR, 718 and graphene-supported single-atom electrocatalysts with different M-N-C coordination patterns. 719 The obtained relationships between the targeted functions/ activities, compositions, and characteristics can further guide the synthesis of optimal materials.…”
Section: Designing Optimized and Scalable Reactorsmentioning
confidence: 99%
“…169 Furthermore, it was suggested very recently that the optimal strain for high ORR performance can vary, depending on the type of core and shell materials and on the particle size. 170 While most core−shell structures have a spherical or polyhedral shape, it was demonstrated that low-dimensional core−shell structures could attain much higher ORR perform- ance. Bu et al reported noticeable improvement of ORR activity in the PtPb/Pt core−shell nanoplate structure with a Pt shell thickness of ∼1 nm, as shown in Figure 14g,h.…”
Section: Orr Catalysis On Metal-based Materialsmentioning
confidence: 99%
“…56 The compressive strain results in a modified GCN that is larger than the original GCN. 57 On the other hand, the ligand effect has not been discussed in literature. During the study of core−shell NPs, preparing a few Pt layers near the surface of the NPs prevents the ligand effect on atomic or molecular adsorption.…”
Section: ■ Introductionmentioning
confidence: 99%